Congenital Diaphragmatic Hernia in Children: A Prospective Study of Clinical Spectrum and Management Outcomes at a Tertiary Care Centre in Northern Bangladesh - Shah Md Ahsan Shahid; Shantona Rani Paul; Zamil Hossain; Nilufar Sharmin; Khondokar Sahely Nasrin Lina; Abdullah Al Mamun; Anowrul Azim; Mst Shamima Nasrin Annee (TAJ: Journal of Teachers Association, 2026)
Background: Congenital diaphragmatic hernia produces a wide clinical spectrum in resource-limited settings, yet prospective outcome data from Bangladeshi paediatric surgical units remain scarce. Objective: This study characterises the clinical spectrum, ventilatory requirement, operative profile, and discharge outcomes of children with congenital diaphragmatic hernia at a Bangladeshi tertiary centre. Methods: A prospective observational study enrolled 49 children with confirmed congenital diaphragmatic hernia at the Department of Paediatric Surgery, Rajshahi Medical College Hospital, between January 2022 and December 2025. Demographic, respiratory, operative, and outcome variables were recorded systematically and analysed using SPSS version 26.0, with categorical variables compared by chi-square or Fisher's exact test and continuous variables by independent-samples t-test. Results: The cohort comprised 30 females and 19 males (male-to-female ratio 1:1.6), with mean age at presentation of 50.5 ± 27.1 months and mean birth weight of 3.22 ± 0.51 kg. Residence was near-evenly split between rural (25/49, 51.0%) and urban (24/49, 49.0%) areas. Left-sided defects predominated (43/49, 87.8%). Respiratory distress was mild in 38 children (77.6%), moderate in 8 (16.3%), and severe in 3 (6.1%); mechanical ventilation was required in only 3 children (6.1%), and ventilator-dependent children presented significantly later than those managed without ventilation (84.3 ± 14.6 vs 48.3 ± 26.3 months, p = 0.031). All 49 children underwent open surgical repair by primary suture closure, with mean operative time of 113.9 ± 22.5 minutes and mean hospital stay of 13.2 ± 4.6 days. Forty-eight children (98.0%) survived to discharge; one death occurred (2.0%). Postoperative complications occurred in 4.1% (2/49: one wound infection, one recurrence), with mean follow-up of 6.5 ± 3.6 months. Conclusion: This cohort demonstrates favourable survival with open repair, low complication rates, and a significant association between later presentation and ventilatory requirement.